Microalgae as functional feed for Atlantic salmon: effects on growth, health, immunity, muscle fatty acid and pigment deposition - Mueller, Jonas; Pauly, Matteo; Molkentin, Joachim; Ostermeyer, Ute; van Muilekom, Doret R.; Rebl, Alexander; Goldammer, Tom; Lindemeyer, Jacqueline; Schultheiß, Thekla; Seibel, Henrike; Schulz, Carsten (Frontiers in Marine Science, 2023)
Microalgae are increasingly being investigated as functional feed additives in a variety of fish species, but our knowledge on how microalgae supplementation affects Atlantic salmon remains limited. We hypothesized that microalgae inclusion of 8% in the feed would improve performance, fatty acid and pigment deposition as well as health and immunity of Atlantic salmon reared in recirculating aquaculture systems (RAS). We fed Atlantic salmon smolts with five different microalgae enriched diets containing Tetraselmis chuii (TC), Arthrospira platensis (AP), Schizochytrium limacinum (SL) or Chlorella vulgaris, either intact (CVI) or as broken cell wall derivative (CVB) or a control diet (CD). After eight weeks of feeding in brackish water (13 psu), all groups were transferred to seawater (32 psu) for additional two weeks. Our results indicate that CVB improved feed conversion and protein retention, but reduced condition factor (p < 0.05) compared to fish fed with a control diet. Voluntary feed intake decreased in seawater, but was similar among diet groups. The amount of docosahexaenoic acid was particularly high in SL-fed fish and alpha-linolenic acid was enriched in fish fed CVI, CVB and TC (p < 0.05). Following seawater transfer, fat content and monounsaturated fatty acids decreased in the muscle, while polyunsaturated fatty acids increased. Lutein was present in all muscle samples, but highest concentrations were found in CVB-, CVI- and TC-fed fish. In the anterior intestine, microalgae supplementation induced differentially regulated trout protein 1 (drtp1) expression in CVI- and CVB-fed fish, but reduced the expression of interleukin 1 and 10 receptor (il1r2 & il10rb) in CVI-fed fish. In the liver, feeding CVI and SL induced complement C1q like 2 (c1ql2) expression, while reducing serum amyloid A5 (saa5) expression. Superoxide-dismutase protein concentration was induced in the liver of fish fed SL, while myeloperoxidase was reduced in most microalgae-fed groups. In conclusion, we show that commercially relevant microalgae can be used as functional feed additives for Atlantic salmon promoting different health aspects without negatively affecting their growth performance when cultivated in RAS.